(untitled) (Journal of Material Science and Technology Research, 2022)
Abstract: The use of thin films to coat mechanical components is a well-established practice. The main uses concern areas in which scratch resistance, corrosion resistance, surface hardness and particular aesthetic characteristics are required. In addition to these properties, it has been demonstrated that Physical Vapor Deposition (PVD) processes bring further benefits from a structural point of view, especially as regards fatigue and contact fatigue phenomena. In this research work, predictive models have been proposed which allow to evaluate the mechanical behavior of coated components to model the initiation and propagation of cracks. Spur gears used in the automotive and motorcycle industries were examined. Therefore, advanced numerical models were developed to accurately evaluate the stress-strain state of the components under examination, both as regards the fatigue at the tooth base and for the contact fatigue on the tooth flank. The results of the numerical models were finally compared with the results of the experimental tests to verify their accuracy.